Permeability effects on unsteady MHD flow of visco-elastic Oldroyd fluid under time varying body force through a rectangular channel in the presence of Hall current - Saxena, Satya Sagar (Journal of Global Research in Mathematical Archives(JGRMA), 2018)
In this paper, an analysis of the effects of permeability of medium on unsteady MHD flow of Oldroyd fluid under time varying body force through a rectangular channel taking Hall current into account is presented. The velocity profiles of a fluid element are discussed theoretically and graphically. From this flow we have also deduced the flow of visco-elastic Rivlin-Ericksen fluid and ordinary viscous fluid. These types of rheological problems are used in factories and industries. The velocity profiles are evaluated numerically and presented graphically using MATLAB for different values of flow parameters.